Review of corpus tools for vocabulary teaching and learning - Ma Qing; Mei Fang (Journal of China Computer-Assisted Language Learning)
This review aims to introduce corpora as useful tools for facilitating vocabulary teaching and learning. Corpora have long been applied to improve learner language learning, but their direct implication in classroom teaching is rare. This review begins with providing basic concepts related to corpora and then illustrates how corpora can benefit language learning and teaching. To make better use of corpora, careful consideration needs to be given to how to choose an appropriate corpus and what specific corpus search functions should be used. To this end, a new corpus-based language pedagogy (CBLP) is introduced as a new pedagogy to integrate corpora into classroom to facilitate teachers’ teaching. CBLP blends corpus linguistics with classroom pedagogy. In addition, four design principles are illustrated to help teachers design effective corpus-based lessons. Finally, a number of important issues are raised to help teachers improve their design of corpus-based lessons.